2019
DOI: 10.1186/s13046-019-1387-5
|View full text |Cite
|
Sign up to set email alerts
|

Activity of BET-proteolysis targeting chimeric (PROTAC) compounds in triple negative breast cancer

Abstract: Background Triple negative breast cancer (TNBC) is an incurable disease where novel therapeutic strategies are needed. Proteolysis targeting chimeric (PROTAC) are novel compounds that promote protein degradation by binding to an ubiquitin ligase. In this work, we explored the antitumoral activity of two novel BET-PROTACs, MZ1 and ARV-825, in TNBC, ovarian cancer and in a BET inhibitor resistant model. Methods OVCAR3, SKOV3, BT549, MDA-MB-231 cell lines and the JQ1 resis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(65 citation statements)
references
References 19 publications
2
63
0
Order By: Relevance
“…Further, BET inhibitors such as JQ1 show a very short half-life, and the concentrations required to mediate single agent activity exceed physiologic safety levels in vivo [ 37 ]. The BRD4 degrader MZ1 potently and rapidly induces preferential removal of BRD4 over BRD2 and BRD3, and has shown high efficacy in ovarian and triple-negative breast cancer in vivo [ 38 ]. The activity of MZ1 is dependent on binding to VHL but is achieved at a sufficiently low concentration not to induce stabilization of the VHL substrate HIF-1α [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further, BET inhibitors such as JQ1 show a very short half-life, and the concentrations required to mediate single agent activity exceed physiologic safety levels in vivo [ 37 ]. The BRD4 degrader MZ1 potently and rapidly induces preferential removal of BRD4 over BRD2 and BRD3, and has shown high efficacy in ovarian and triple-negative breast cancer in vivo [ 38 ]. The activity of MZ1 is dependent on binding to VHL but is achieved at a sufficiently low concentration not to induce stabilization of the VHL substrate HIF-1α [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…To explore the role of cooperativity in ternary complex formation, the Ciulli group studied PROTAC-induced degradation of the BET protein family (BRD2, BRD3, BRD4) ( 83 ), a protein family extensively studied in the PROTAC field ( 27 , 60 , 73 , 74 , 81 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 ). Using SPR and ITC, they found that ternary complexes with positive cooperativity (BRD4 BR2 :PROTAC MZ1:VHL; α = 22) caused more efficient cellular degradation than complexes with negative cooperativity (BRD4 BR2 :PROTAC MP61:VHL; α = 0.2).…”
Section: Hijacking Of the Ups: Protacsmentioning
confidence: 99%
“…[ 144 ] BRD4 is a member of the BET protein family, and the PROTAC ARV‐825, which was constructed with the BRD4 inhibitor OTX015 and the CRBN ligand pomalidomide, was shown to selectively degrade BRD4 in Burkitt's lymphoma, triple‐negative breast cancer, multiple myeloma, and cholangiocarcinoma cells. [ 129,145–147 ] Interestingly, ARV‐825 also plays an important role in the treatment of vemurafenib‐resistant melanoma. [ 148 ] Another BRD4‐targeted PROTAC ARV‐771 was synthesized with a BRD4 inhibitor and VHL ligand and experimental results showed rapid degradation of BRD2/3/4 in castration‐resistant prostate cancer.…”
Section: Strategies For Selective Protein Degradationmentioning
confidence: 99%